Walking Backwards and Sideways: The Transmigrations of the Poet in Shirley Geok-lin Lim’s Work - Newton, Southern Methodist University, USA, Pauline T. (Asiatic: IIUM Journal of English Language and Literature, 2014)
This article and interview unveil ways in which Shirley Geok-lin Lim addresses her status as a transnational wanderer in recent poetry, specifically in Walking Backwards: New Poems (2010), noting relevance to earlier fictional works such as Joss and Gold (2001). For the brief interview, I asked Lim in July 2013 to elaborate on and to clarify some of her statements in her poems that might prove cryptic to a reader unfamiliar with Chinese customs.